PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Mufidah, Nur Mufidah; Purnamasari, Puji Endah (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2018)
Increasing the firm value is a key point for firm to attract investors. The firm value is very important because it becomes a benchmark of firm performance, the firm value in addition is influenced by profitability, investors also see the effect of the firm or form of firm Social Responsibility in the firm. The purpose of this study is to determine the effect of profitability toward firm value, firm Social Responsibility moderate the relationship of profitability toward firm value and Good Corporate Governance moderate the relationship of profitability toward the firm value. The population in this study is a state-owned firm listed on the BEI in 2012-2016. The technique of sampling uses purposive sampling and based on criteria that have been done then the number of samples are obtained as many as 12 samples of state-owned enterprises. The experiment hypothesis of the research used multiple linear regression analysis techniques and Moderating Regression Analysis (MRA) with SPSS application. The results of this study indicate that profitability variables have a positive and significant effect on firm value, the disclosure of Corporate Social Responsibility does not moderate the relationship of return on assets to firm value, firm Social Responsibility strengthens the relationship of return on equity to firm value and Good firm Governance does not moderate profitability relation to firm value.